Acceptance and attitudes towards COVID-19 vaccination during pregnancy in Canada - Suraya Bondy; Elisabeth McClymont; Gal Av-Gay; Arianne Albert; Janice Andrade; Sandra Blitz; Ianna Folkes; Lucia Forward; Erin Fraser; Sela Grays; Jon Barrett; Julie Bettinger; et al. (Human Vaccines & Immunotherapeutics)
The COVID-19 pandemic posed a unique set of risks to pregnant women and pregnant people. SARS-CoV-2 infection in pregnancy is associated with increased risk of severe illness and adverse perinatal outcomes. However, evidence regarding the use of COVID-19 vaccines in pregnancy shows safety and efficacy. Despite eligibility and recommendations for COVID-19 vaccination among pregnant women and pregnant people in Canada, uptake remains lower compared to the general population, warranting exploration of influencing factors. The COVERED study, a national prospective cohort, utilized web-based surveys to collect data from pregnant women and pregnant people across Canada on COVID-19 vaccine attitudes, uptake, and hesitancy factors from July 2021 to December 2023. Survey questions were informed by validated tools including the WHO Vaccine Hesitancy Scale (VHS) and the Theory of Planned Behavior (TPB). Of 1093 respondents who were pregnant at the time of the survey, 87.7% received or intended to receive a COVID-19 vaccine during pregnancy. TPB variables such as positive attitudes toward COVID-19 vaccines (OR = 1.11, 95% CI = 1.08–1.14), direct social norms, and indirect social norms were significantly associated with vaccine acceptance. Perceived vaccine risks, assessed by the WHO VHS, were greater in those not accepting of the vaccine. Our study identified several key factors that play a role in vaccine uptake: perceived vaccine risks and safety and social norms. These findings may guide public health recommendations and prenatal vaccine counseling strategies.